Model and experiment analysis of 1.2 kW PEMFC electrification - Chanpeng W. (2014)
This paper developed a model of PEMFC by using MATLAB/Simulink in order to analyze the operation performance of a Proton Exchange Membrane Fuel Cell of 1.2 kW. Also, the experimental is set up to study the performance of PEMFC. The results show that the operation performance of fuel cell depends on gas pressure, operation temperature, gas flow rate and gas humidity. All parameters which affected the system performance are evaluated. The results of both an experiment and model simulation are determined. The experimental results show the behavior of PEMFC when there is load changing. All aspects of PEMFC electrification will be fully investigated in order to develop the alternative sustainable PEMFC energy sources and to study the fundamental of fuel cell technology. The results of simulation and experimental will be compared.